Mereology and Truth-Making - SIMONS, PETER (My University, 2015)
M any mereological propositions are true contingently, so we are entitled to ask why they are true. One frequently given type of answer to such questions evokes truth-makers, that is, entities in virtue of whose exis- tence the propositions in question are true. However, even without endors- ing the extreme view that all contingent propositions have truth-makers, it turns out to be puzzlingly hard to provide intuitively convincing candidate truth-makers for even a core class of basic mereological propositions. Part of the problem is that the relation of part to whole is ontologically intimate in a way reminiscent of identity. Such intimacy bespeaks a formal or internal relation, which typically requires no truth-makers beyond its terms. But truth-makers are held to necessitate their truths, so whence the contingency when A is part of B but need not be, or B need not have A as part? This paper addresses and attempts to disentangle the conundrum.
Keywords: mereology; mereological propositions; truth-makers; continuants; MEREOLOGY; truth-makers